Urban and regional economics - McCann, Philip, 1964- (Oxford ; New York : Oxford University Press, 2001)
Provides an integrated framework for the study of urban and regional economics. This book provides an introduction to the main foundational models, principles, and theories of the subject, including Classical, Neo-classical, and Keynesian approaches, and uses a range of international examples to illustrate the ideas being explained.
Includes bibliographical references (p. [269]-276) and index.
oif 31/07/14; 01/04/15
Loan
Keywords: Urban economics; Regional economics